A history of drinking : the Scottish pub since 1700 - Cooke, Anthony, 1943- (Edinburgh University Press, 2015)
A social history of Scottish drinking and drinking establishments. What did Samuel Johnson, James Boswell, Dorothy Wordsworth, James Hogg and Robert Southey have in common? They all toured Scotland and left accounts of their experiences in Scottish inns, ale houses, taverns and hotels. Similarly, poets and writers from Robert Burns and Walter Scott to Ian Rankin and Irvine Welsh have left vivid descriptions of the pleasures and pains of Scottish drinking places. Pubs also provided public spaces for occupational groups to meet, for commercial transactions, for literary and cultural activities and for everyday life and work rituals such as births, marriages and deaths and events linked with the agricultural year. These and other historical issues such as temperance, together with contemporary issues, like the liberalisation of licensing laws and the changing nature of Scottish pubs, are discussed in this fascinating book. The book is bought up to the present day by a case study of present day licensees, based on interviews with a range of licensees across Scotland, looking at their experience of the trade and how it has changed in their working lives. Key Features. Considers pubs as public spaces and casts light on issues such as the rise of voluntary associations, clubs and societies and the economic functions of pubs. Places Scottish drinking places in an anthropological context to examine their role in everyday life, community and work rituals. Discusses the temperance movement and responses to it. Interviews with present day licensees across Scotland bring the book down to the present and considers the future of the Scottish pub.